AN ANALYSIS OF PHONOLOGICAL FEATURES OF AUTISTIC CHILDREN - Gusnelia, Aisya (2015)
The present study seeks to investigate the phonological features of children with impairments, particularly children with the autism spectrum disorder (ASD). In this study, phonological investigation was performed on four autistic children, 9-10 years old, including three boys and one girl. Data were obtained from two different tasks: spontaneous speech and single-word production. Data were analyzed qualitatively supported by descriptive quantification. The findings show that Indonesian autistic children fail to produce three classes of sounds correctly including plosive, nasal, and liquid sounds, particularly plosive /p/ and /k/, nasal /n/ and /ŋ/, and liquid /r/ and /l/. The findings do not in line with the earlier studies by Fatmasari (2011) and Pangestuti (2011) but support and extend Cleland et al.'s (2010) study showing that the speech of autistic children was characterized by mainly substitution and reduction processes (liquid deletion and liquid to liquid substitution most frequently). An interesting characteristic also emerged, suggesting that autistic children tend to have word-final coda deletion in their speech sound production. Furthermore, this study also suggests that autistic children produce sounds better in the form of spontaneous speech than single-word production. Keywords: Psycholinguistics, phonology, phonological patterns, sound production, children, autism. Penelitian ini bertujuan untuk menyelidiki fitur fonologis pada anak berkebutuhan khusus, tepatnya anak dengan gangguan spektrum autisme (ASD). Dalam penelitian ini, investigasi fonologi dilakukan pada 4 anak autis, 9-10 tahun, terdiri atas 3 laki-laki dan 1 perempuan. Data diperoleh dari dua cara: ujaran spontan dan produksi kata tunggal. Data dianalisis secara kualitatif dengan menggabungkan statistik deskriptif. Temuan menunjukkan bahwa anak autis gagal memproduksi 3 jenis bunyi dengan sempurna, yaitu bunyi plosif, nasal, dan liquid, tepatnya plosive /p/ dan /k/, nasal /n/ and /ŋ/, dan liquid /r/ dan /l/. Penemuan ini berbeda dengan studi sebelumnya oleh Fatmasari (2011) dan Pangestuti (2011) namun mendukung dan memperluas penemuan Cleland dkk (2010) dengan menunjukkan bahwa bicara anak autis ditandai terutama dengan proses substitusi dan reduksi (liquid deletion dan liquid to liquid substitution muncul paling sering). Satu karakteristik menarik juga muncul bahwa anak autis cenderung melakukan word-final coda deletion dalam produksi ujarannya. Lebih lanjut, studi ini juga menunjukkan bahwa anak autis memproduksi bunyi lebih baik dalam bentuk ujaran spontan dari pada dalam bentuk produksi kata tunggal. Kata Kunci: Psikolinguistik, fonologi, pola fonologi, produksi bunyi, anak-anak, autis.